2018
DOI: 10.1002/jcp.26761
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Runx2 in condylar chondrocytes disrupts TMJ tissue homeostasis

Abstract: Runt-related transcription factor-2 (Runx2) is essential for chondrocyte maturation during cartilage development and embryonic mandibular condylar development. And the process that chondrocytes, especially a subgroup of hypertrophic chondrocytes (HC), could transform into bone cells in mandibular condyle growth makes chondrocytes crucially important for normal endochondral bone formation. To determine whether Runx2 regulates postnatal condylar cartilage growth and tissue homeostasis, we deleted Runx2 in chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Our previous studies demonstrated that Agc1-CreER T2 mice could efficiently drive Cre expression in TMJ cells. 26 , 49 Cre-negative littermates were used as the control group. β-catenin Act mice and Cre-negative littermates (male) were administered tamoxifen (Sigma, St. Louis, MO, USA) by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies demonstrated that Agc1-CreER T2 mice could efficiently drive Cre expression in TMJ cells. 26 , 49 Cre-negative littermates were used as the control group. β-catenin Act mice and Cre-negative littermates (male) were administered tamoxifen (Sigma, St. Louis, MO, USA) by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple transcription factors (TFs) and signaling pathways regulate hypertrophic chondrocyte-specific Col10a1 expression in vitro and in vivo (Lu et al, 2014). Of these, Runx2 is essential for osteoblast differentiation and chondrocyte hypertrophy (Komori et al, 1997;Lee et al, 1997;Otto et al, 1997;Komori, 2018;Liao et al, 2019;Qin et al, 2020) and is a major transcriptional determinant for Col10a1 expression across species (Drissi et al, 2003;Simoes et al, 2006;Higashikawa et al, 2009). In our work on mouse Col10a1 regulation, we found that Runx2 directly interacts with the Col10a1 proximal promoter and 150-bp enhancer and is an indispensable Col10a1 regulator (Zheng et al, 2003(Zheng et al, , 2009Li et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…Interestingly, Runx2 deletion blocks chondrocyte translocation into the subchondral bone region and inhibits chondrocyte transdifferentiation into progenitor cells [ 89 ]. Comparatively, histological analysis demonstrated extensive chondrocyte growth in condylar cartilage and subchondral bone in control mice, indicating a key role for Runx2 in subchondral bone remodeling [ 89 ]. Runx2 was also highly expressed in proliferative and hypertrophic chondrocytes, suggesting Runx2 regulates subchondral bone remodeling.…”
Section: Runx2 Functions In Different Joint Tissuesmentioning
confidence: 99%